2003
DOI: 10.1007/s10350-004-6677-z
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Immunologic Effects of Preoperative Chemoradiotherapy in Advanced Rectal Cancer

Abstract: Preoperative chemoradiotherapy for advanced rectal cancer results in a significant preoperative and postoperative immune dysfunction as indicated by depression of lymphocyte subpopulations, monocytes, granulocytes, and proinflammatory cytokine release. These findings are of importance because increased perioperative morbidity and mortality rates have been observed after preoperative chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 36 publications
(44 reference statements)
4
39
0
1
Order By: Relevance
“…Chemotherapy-induced side effects are similar to those seen in the sickness behavior attributed to proinflammatory cytokine release (Wood, Nail, Gilster, Winters, & Elesea, 2006). A variety of antineoplastic agents induce production of proinflammatory cytokines in various cell lines in vitro (Maier & Watkins, 2003;Niiya et al, 2003;Wichmann, et al, 2003;Zaks-Zilberman, Zaks, & Vogel, 2001). The taxanes (paclitaxel and docetaxel) have been associated with increased plasma levels of interleukins 6, 8, and 10 (Ahles & Saykin, 2007).…”
Section: Chemotherapy-related Cognitive Impairmentmentioning
confidence: 79%
“…Chemotherapy-induced side effects are similar to those seen in the sickness behavior attributed to proinflammatory cytokine release (Wood, Nail, Gilster, Winters, & Elesea, 2006). A variety of antineoplastic agents induce production of proinflammatory cytokines in various cell lines in vitro (Maier & Watkins, 2003;Niiya et al, 2003;Wichmann, et al, 2003;Zaks-Zilberman, Zaks, & Vogel, 2001). The taxanes (paclitaxel and docetaxel) have been associated with increased plasma levels of interleukins 6, 8, and 10 (Ahles & Saykin, 2007).…”
Section: Chemotherapy-related Cognitive Impairmentmentioning
confidence: 79%
“…34 Molecular studies have further contributed to the understanding of the possible detrimental effects of neoadjuvant CRT to patient's immunology. 35 Significant decreases in both pro-inflammatory cytokines, such as interleukin-6 precursor (IL-6) and tumor necrosis factor alpha (TNF-α), Figure 2 Overall survival according to the presence of peritumoral inflammatory infiltrate. Five-year overall survival rates were 80.6 and 90.5% for patients with negative and positive peritumoral inflammatory infiltrate, respectively (p=0.55).…”
Section: Discussionmentioning
confidence: 99%
“…and markers of cell-mediated immunologic response including specific lymphocyte subpopulations, granulocytes, and monocytes in patients managed by neoadjuvant CRT have been documented. 35 These results are of clinical interest, as these specific cells have been demonstrated to interfere with tumor cell growth during surgical manipulation. 36,37 Patients in this same study undergoing neoadjuvant CRT had CD4+ cell counts <200 μl, similar to patients with HIV infection considered to be advanced immune-impaired and requiring adjuvant immunological therapy.…”
Section: Figurementioning
confidence: 92%
“…Patients with immunological dysfunction (advanced liver disease, human immunodeficiency virus infection, hepatitis B or C virus infection), use of steroids or high preoperative C-reactive protein (CRP) levels ([3.0 mg/dL) were excluded from this study. Patients who had undergone preoperative chemoradiotherapy and chemotherapy were also excluded, because many studies [17][18][19] have reported that chemoradiotherapy or radiotherapy suppresses the perioperative inflammatory response. All participating patients underwent colorectal surgery at the Department of Surgical Oncology of the University of Tokyo Hospital.…”
Section: Methodsmentioning
confidence: 99%